Implikatur Kampanye Calon Walikota dan Wakil Walikota Bengkulu - Putra, Rian Surya (Jurnal Lentera (Jurnal Pendidikan dan Pengajaran Bahasa Indonesia), 2019)
This research aims to describe the purpose and the function of the candidate of mayor and deputy mayor’s campaign discourse implicature in Bengkulu for 2012 – 2017 period. The method used was descriptive method. The result showed that the implicature occurred on the campaign discourse was aimed to persuade and influence the readers. There are some purpose of this implicature, those are: (1) to promise the flagship program, (2) to assure people towards the candidate that is going to be voted, (3) to persuade people to vote the candidate, (4) to satirize. Additionally, the functions of the implicature are: (1) to make people agree with the program which is offered, (2) to persuade people to vote the candidates, (3) to criticize. Key Words: Discourse, Implicature, the candidate of mayor in Bengkulu